(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Blockchain technology has now become one of the essential financial technologies that cannot be dispensed with and has been used to address various topics, including health, real estate, etc, this study aimed to demonstrate the impact of blockchain technology in achieving the first objective of internal control, which is operational objectives, this research explores the importance of this technology and how it can affect internal control, this research follows the descriptive and analytical approach, A questionnaire was distributed to the research sample consisting of academics, auditors, accountants, and computer specialists, the sample amounted to 40 people, The questionnaire was published via Google Forms, and the SPSS program was used for statistical analysis, the results indicated that the use of blockchain technology will achieve the first objective, which is operational objectives.